Analisis Peran Aktor dalam Upaya Modernisasi Kerangka Berpikir Masyarakat Dusun Jambuan - Noorma Mega Astinaningrum; Aldiansa Roby Juniardi; Wanda Aziza (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Modernization is a change that cannot be avoided by all levels of society. The research aims to examine the role of actors in embracing the people of Jambuan Hamlet who have a traditional frame of mind and previous habits toward a more modern life. This research is descriptive qualitative research, namely the data collected was obtained through in-depth interviews with vital informants and supporting informants. The results of the research show the socio-cultural background of the Jambuan Hamlet community. Society has a pragmatic mindset or instantaneous thinking which is motivated by a lack of education knowledge which impacts skills in the field of work as well as a lack of understanding of religious knowledge. The role of actors here can be seen in seeking modernization of the social aspects of the residents of Jambuan Hamlet. This change can be seen in changes in the minimum standards of education, the deepening of religion, and the framework of thinking in the people of Jambuan Hamlet.